INNOVATIONS OF SPECIAL TAX REGIMES FOR SMALL BUSINESS IN 2017. TRANSITION OF INSURANCE PREMIUMS TO TAX AUTHORITIES - A. Lukashevich (Вестник университета)
Small business, contributing to the creation of new jobs, and performs a number of important socio-economic tasks, therefore, for its development and support in economically developed countries used different systems of tax exemptions, simplification of accounting and filing of tax reports. The article examines changes from 2017 in special tax regimes for small business entities related to the conditions of their application. The features of taxation of insurance contributions for compulsory pension, social and medical insurance for small businesses. Special attention is paid to analysis of problems encountered by taxpayers in connection with the innovations.